PENETAPAN KADAR VITAMIN C PADA BROKOLI PUTIH (Brassica oleracea L.) YANG BEREDAR DI KECAMATAN DELI TUA DENGAN METODE SPEKTROFOTOMETRI UV-VIS - Purba, Jhan Saberlan; Br Sembiring, Tio Ranti Sari (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2026)
White broccoli (Brassica oleracea L.) is a vegetable rich in vitamin C and has potential as a functional food source beneficial to health. This study aimed to determine the vitamin C content in white broccoli available in Deli Tua District using the UV-Vis spectrophotometric method and to evaluate the validity of the applied analytical method. The broccoli sample was extracted, analyzed qualitatively using iodine reagent, and quantitatively at a maximum wavelength of 265 nm. The calibration curve was constructed using five standard concentrations of vitamin C with a regression equation of y = 0.0495x + 0.0019 and a correlation coefficient r = 0.9996, indicating excellent linearity. The analysis showed that the vitamin C content was 1,8098 mg/g. The method validation met the required criteria: accuracy % recovery of 108.36%, precision RSD 0.47739%, limit of detection LOD of 0.18375, and limit of quantification LOQ of 0.61325. Therefore, the UV-Vis spectrophotometric method is proven valid and accurate for determining the vitamin C content in white broccoli.